2019
DOI: 10.1111/are.14288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Bergamot ( Citrus bergamia ) peel oil on growth, haematology and immune response of European sea bass ( Dicentrarchus labrax ) juveniles

Abstract: The aim of the present study was to evaluate the effects of essential oil extracted from bergamot (Citrus bergamia) peel on growth performance and health status of European sea bass juveniles (5.10 + 0.05 g). Test diets supplemented with 0.0%, 0.5%, 1.0% and 2.0% bergamot peel oil (BPO0, BPO0.5, BPO1 and BPO2) were fed to experimental fish for 60 days. At the end of the experiment, the best growth performance was obtained in the BPO0.5 and BPO1 groups (p < .05). No significances were found for haematological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
(66 reference statements)
4
15
0
Order By: Relevance
“…The results from the present study revealed that Nile tilapia fed diets supplemented with different inclusion levels of EOs extract from sweet orange and/or lemon peels revealed improved growth (final fish weight, BWG, WG%, SGR and TGC) and reduced FCR compared with CG, and the proper growth and feed utilization being directed towards the fish fed OEO × LEO in a dose‐dependent effect. Similar findings are observed in European sea bass ( Dicentrarchus labrax ) juveniles (Acar et al., 2019), Mozambique tilapia ( Oreochromis mossambicus ) (Acar et al., 2015), Rainbow Trout ( Oncorhynchus mykiss ) juveniles (Gültepe, 2018), silver catfish ( Rhamdia quelen ) (Lopes et al., 2019), Juvenile Labeo victorianus fingerlings (Ngugi et al., 2017) and Nile tilapia ( Oreochromis niloticus ) fingerlings (Salem & Abdel‐Ghany, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results from the present study revealed that Nile tilapia fed diets supplemented with different inclusion levels of EOs extract from sweet orange and/or lemon peels revealed improved growth (final fish weight, BWG, WG%, SGR and TGC) and reduced FCR compared with CG, and the proper growth and feed utilization being directed towards the fish fed OEO × LEO in a dose‐dependent effect. Similar findings are observed in European sea bass ( Dicentrarchus labrax ) juveniles (Acar et al., 2019), Mozambique tilapia ( Oreochromis mossambicus ) (Acar et al., 2015), Rainbow Trout ( Oncorhynchus mykiss ) juveniles (Gültepe, 2018), silver catfish ( Rhamdia quelen ) (Lopes et al., 2019), Juvenile Labeo victorianus fingerlings (Ngugi et al., 2017) and Nile tilapia ( Oreochromis niloticus ) fingerlings (Salem & Abdel‐Ghany, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…This was accompanied by an increase in the secretion of pancreatic digestive enzymes (trypsin and amylase) and intestinal enzymes (maltase, alkaline phosphatase and leucine amino peptidase) (Jang et al., 2007). Furthermore, EOs may improve the beneficial microbial population (Acar et al., 2019; Jang et al., 2007) and reduce bacterial count of undesirable and/or pathogenic microorganisms (Salem et al., 2019) in the digestive tract that increases the absorption of essential nutrients (Holst & Williamson, 2008). The reduced pathogenic microorganisms may be attributed to the presence of citral and terpinene as active components of OEO and LEO that have antimicrobial activities (Kumar et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to reducing resistance phenomenon (Dugo & Di Giacomo, 2002) and broad‐spectrum antimicrobial activity against fish pathogens, they are considered safe substances with several potential benefits for fish farming, which include the improvement of fish welfare, health and zootechnical performance indices, such as growth performance, feed conversion rate and protein efficiency rate (Acar et al., 2019; De Souza et al., 2019; Sutili et al., 2018). The antibacterial (Vaseeharan et al., 2013), antiparasitic (Da Costa et al., 2017; Metin et al., 2015; Soares et al., 2016) and immunomodulatory (Acar et al., 2019; Sutili et al., 2018; Valladão et al., 2017) effects of EOs help to prevent outbreak of disease in fish farming, therefore minimizing economic loss due to disease and help combat the indiscriminate use of antimicrobials and therefore the emergence of antimicrobial resistance. Moreover, the reduction of antimicrobial utilization in aquaculture has the potential to improve the quality of aquaculture products by reducing antimicrobial residue in both the environment and animals intended for human consumption (Liu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%